The Climate Data Tool: Enhancing Climate Services Across Africa - Dinku, Tufa; Faniriantsoa, Rija; Islam, Shammunul; Nsengiyumva, Gloriose; Grossi, Amanda (Frontiers in Climate, 2022)
Climate services can contribute to alleviating a range of climate-sensitive development challenges, including those of agricultural production and food security. However, the use of climate data for research and applications in Africa has been scanty, mainly due to poor availability of and access to quality climate data. Weather stations are sparse, and their number has been declining. Access to existing climate data is a challenge mainly because of national data policies, low financial investment, lack of dissemination capacity and tools, and high access costs. The ENACTS (Enhancing National Climate Services) initiative led by the International Research Institute for Climate and Society (IRI) at Columbia University has been tackling this problem by working with National Meteorological Services (NMS) in Africa and in other developing countries. This initiative helps NMS to improve data availability and quality, by combining quality-controlled data from national observation networks with satellite estimates for rainfall and climate model reanalysis products for temperature. This requires access to an easy-to-use and freely available tool for performing the tasks required to generate the data, as well as using the generated data. Most NMS in Africa does not have access to such a tool. To meet this significant need, the IRI developed such a tool in-house. This is the Climate Data Tool (CDT), which is an open-source, R-based software with an easy-to-use a graphical user interface (GUI). It can be used for data organization, quality control, combining station data with satellite and reanalysis data, evaluating merged and inputs datasets, performing an array of analyses, and visualization. The CDT software has been evolving over the last seven years with inputs from the NMS themselves. Now, it has become a powerful and user-friendly tool, and has been installed in over 20 countries in Africa alone.